السياحة في ليبيا ومتطلبات تنميتها دراسة تحليلية باستخدام نموذج بورتر للقوى الخمسة - بن سعود رحاب محمد (Scientific Journal of University of Benghazi, 2019)
act The tourism sector is one of the important ways to achieve the integrated economic development through the compatibility between the various productive and services sectors to make progress in quality and level of life. Libya has a rich tourism potential، which can be utilized to fuel economic growth. It has delightful coastline of coral، beach، and wonderful interior topography of mountains، desert. In context of nature، the country witnesses good sunshine and clear sky conditions. However، globally Libya is not a well-known tourist destination. This study aimed to explore the characteristics of the Libyan tourism sector. Also it aimed to explore what the major problems this sector faced . The paper also provides some recommendations that need to be considered by policy makers and incorporated into any future development plans on the Libya tourism industry. Porters Five Forces model was used to analyze tourism sector. The study concluded that tourism has many characteristics، but many countries may not have them، whereas other countries have them but can’t use them well. Libya has many tourist factors but doesn’t utilize them properly، there was neither real tourism industry، nor effective tourism investment. Tourism in Libya is still chaotic and purposeless، and unplanned.